Psychomotor profile of scholarly children (6 and 10 years old) in Pereira city, Colombia - Calero Saa, Pedro Antonio (Revista de Educação Física / Journal of Physical Education, 2016)
Introduction: The psychomotor profile of children is directed related to the psychomotor development, understood as a process of continuous evolution that happens over the years. Objective: This article attempts to determine the psychomotor profile of children aged between 6 and 10 years, from educational institutions in the city of Pereira, Risaralda (Colombia). Methods: Through a cross descriptive quantitative study with a comparative phase, 26,448 children were eligible to participate the study, meeting the inclusion criteria. From them, a sample of 420 children aged between 6 and 10 years was selected, obtained from the formula for finite populations, with a prevalence of 44% of reference; sampling was a simple random. The instrument used was the Vitor da Fonseca’s test battery of psychomotor development. Chi-square was used to evaluate association of age, education level and residential community with level of confidence of 95%. Results: The sample was composed of 222 girls (52.9%; CI 47-56) and 198 boys (47%; CI 42-51). 90.2% (95%CI 87-92) presented psychomotor profile classified as Good (Eupraxic) while 4.0% (95%CI 3-4) were on Satisfactory (Dyspraxic) range and 5.7% (95%CI 4-5) exhibited Excellent (Hyperpraxic) psychomotor profile. Conclusion: In general, the children evaluated presented adequate psychomotor development. Results according to the factors (Tonicity, Laterality, Body Notion, Balance, Time Space, Global Praxia and Fine Praxia) were discussed. Perfil psicomotor de crianças em idade escolar (entre 6 e 10 anos) da cidade de Pereira, Colômbia Introdução: O perfil psicomotor da criança está diretamente relacionado com o desenvolvimento psicomotor, o qual é entendido como um processo de evolução contínua que acontece à medida que os anos passam. Objetivo: Este artigo buscou determinar o perfil psicomotor de crianças com idade entre 6 e 10 anos, das instituições de ensino dentro da cidade de Pereira, Risaralda (Colômbia). Métodos: Um estudo descritivo quantitativo foi realizado, com a participação de todas as escolas de Pereira: 26.448 crianças preencheram os critérios de inclusão, sendo, portanto, elegíveis para participar do estudo. Destas, uma amostra de 420 crianças com idades entre 6 e 10 anos foi selecionada pelo método de amostragem aleatória simples para populações finitas, com uma prevalência de 44% de referência. Para avaliar o desenvolvimento psicomotor foi utilizado a bateria de testes de Vitor da Fonseca. O teste Qui-quadrado foi utilizado para avaliar a associação de idade, escolaridade e comunidade residencial com nível de confiança de 95%. Resultados: A amostra foi composta por 222 meninas (52,9%; IC 47-56) e 198 meninos (47%; CI 42-51). 90,2% (95% IC 87-92) dos participantes apresentaram perfil de desenvolvimento psicomotor classificado como Bom (Eupráxico); 4,0% (IC 95% 3-4) apresentaram perfil Satisfatório (Dispráxico) e 5,7% (IC95% 4-5) exibiram perfil de desenvolvimento psicomotor Excelente (Hiperpráxico). Conclusão: Em geral, as crianças avaliadas apresentaram desenvolvimento psicomotor adequado. Os resultados segundo fatores (Tonicidade, Lateralidade, Noção Corporal, Equilíbrio, Espaço de Tempo, Praxia Global e Praxia Fina) foram discutidos.